Pluri-versalismo transmoderno decolonial in the crisis civilizatory:A fixed reading to Grosfoguel - Canaza Choque, Franklin Américo (2019)
The enormous burden that represents the planetary crisis to which humanity has brought it on a canon epistemic occidentalocéntrico requires a replica. For Ramón Grosfoguel, to change the geopolitics of knowledge of the modern world system/ colonial capitalist/ patriarchal by a look and positioning structural from the pluriversalismo transmoderno decolonial, is to find in the package of power relations not only contents economic, political and military, but a wide range of articulations that were buried by a eurocentric modernity. In this theoretical-reflective text is analyzed in a concise way the deployment of the studies of Grosfoguel, who is positioned within the framework of decolonization and of a critical dialog intercultural North-South Global. Apodícticamente, its decolonial cut is a rupture with the monotopic universalism eurocentric.